Perbedaan Jumlah Trombosit Pada Darah EDTA Yang Segera Diperiksa dan Penundaan Selama 1 Jam di Laboratorium RSJ Grhasia Yogyakarta - sujud sujud; ratih hardiasari; anik nuryati (Medical Laboratory Technology Journal, 2015)
Pre-analytical phases is a very important stage and need to be considered properly. Pre-analytical phases of which is the process of blood sampling, sample delivery, the inclusion of the type of inspection, sample preparation and selection tools. A fact which still often the case that their neglect by nurses or laboratory personnel in taking and processing the blood samples. Blood samples for examination platelet counts as much as possible is done properly and the sample must be examined in less than 1 hour after taking blood. Delays checks can cause a decrease in platelet count. Delays often occur for over an hour due to the shipment of samples from wards that are not immediately performed or work shift lab personnel. The aim of research to determine the difference in the number of platelets in the blood EDTA is immediately checked and a delay of 1 hour by using KX-21 Hematology analyzer. Experimental study design with pre- and post-test study without control. The study was conducted at the Laboratory of RSJ Grhasia Yogyakarta, with the object of research is venous blood from patients RSJ Grhasia between the ages of 20-50 years of both men - men and women. Data were analyzed parametric statistical tests Paired samples t-test. The results of significant research value of the results of parametric statistical tests Paired samples t-test was 0,000 (sig